Narcissism, perfectionism, and self-promoting behavior on social networking sites among university students in Pakistan - Abbasi, Najam ul Hasan; Arshad, Qaisar; Wang, Tao; Hadi, Abdul (Anales de Psicología / Annals of Psychology, 2024)
There is considerable debate in the literature about how narcissism predicts various behaviors associated with the utility of social networking sites, but researchers have paid less attention to exploring the potential mediators of this relationship. Based on the existing literature, we anticipated that narcissism predicts self-promoting behaviors on social networking sites. The current study also investigated the mediating role of multidimensional perfectionism between narcissism and self-promoting behavior. A total of 605 complete questionnaires were gathered from students from universities from Rawalpindi and Islamabad, Pakistan using convenient sampling. The study used Narcissistic Personality Inventory (Ames et al., 2006), self-developed Self-promoting Behavior on social networking sites questionnaire, and the Multidimensional Perfectionism Scale (Hewitt et al., 1991). Findings indicated that females as compared to males and single as compared to married individuals scored higher on narcissism. Higher educational levels were associated with higher rates of narcissism. The results also suggest that narcissism correlated with self-oriented perfectionism, and more significantly with others-oriented narcissism. Self-oriented and others-oriented perfectionism significantly mediated the relationship between narcissism and self-promoting behavior on social networking sites.